1983
DOI: 10.1128/iai.39.3.1307-1315.1983
|View full text |Cite
|
Sign up to set email alerts
|

Role of type 1 fimbriae in the pathogenesis of ascending urinary tract infection induced by escherichia coli in mice

Abstract: Escherichia coli mutants defective in the ability to agglutinate guinea pig erythrocytes (HA-) were isolated from a nalidixic acid-resistant derivative, 31-B, of E. coli TN 675 that produces type 1 fimbriae and induces urinary tract infection in mice fed a 5% glucose solution. All nine HAmutants were defective not only in their ability to agglutinate Candida albicans cells and erythrocytes from various species, but also in their capacity to adhere to mouse bladder epithelial cells. None of the mutants were agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(40 citation statements)
references
References 31 publications
3
33
1
3
Order By: Relevance
“…37,39 Attachment to and colonization of the mucosal surface of the GIT is aided by the presence of fimbriae, the most common being type 1 and type 3 fimbriae. 42 In addition, the KPF-28 fimbriae, has also been recognized to be involved in adhesion as demonstrated by in vitro experiments on human carcinoma and intestinal cell lines. 43 Apart from adhesion, the fimbriae is also involved in biofilm formation which increases the virulence of the bacteria by enabling the enclosure of bacteria within a dense polysaccharide matrix, thus shielding it from the host immune responses and digestive enzymes secreted within the GIT.…”
Section: Pathogenic Mechanisms and Virulence Factors Of K Pneumoniae Imentioning
confidence: 99%
“…37,39 Attachment to and colonization of the mucosal surface of the GIT is aided by the presence of fimbriae, the most common being type 1 and type 3 fimbriae. 42 In addition, the KPF-28 fimbriae, has also been recognized to be involved in adhesion as demonstrated by in vitro experiments on human carcinoma and intestinal cell lines. 43 Apart from adhesion, the fimbriae is also involved in biofilm formation which increases the virulence of the bacteria by enabling the enclosure of bacteria within a dense polysaccharide matrix, thus shielding it from the host immune responses and digestive enzymes secreted within the GIT.…”
Section: Pathogenic Mechanisms and Virulence Factors Of K Pneumoniae Imentioning
confidence: 99%
“…1). Iwahi et al (1983) demonstrated that the binding of uropathogenic Escherichia coli to mouse bladder cells is mediated by type 1 fimbriae (10). Having established the presence of type 1 fimbriae on strain V and type 1 and type 3 fimbriae on strain A an investigation was carried out to determine their role in the adherence of S. enteritidis to the host epithelial cells.…”
Section: Ld50mentioning
confidence: 99%
“…In another approach, the infectivity of pairs of bacterial variants or phenotypes, only one of which expresses the type 1 fimbrial lectin, were examined. This approach was used in studies of gastrointestinal infection induced by S. typhimurium in mice [33], as well as of urinary tract infection induced by K. pneumoniae in rats [29] or by E. coli in mice [34]. In all cases, the infectivity of the fimbriated phenotype was several times higher than that of the non-fimbriated one.…”
Section: Initiation Of Infectionmentioning
confidence: 99%